Enhancing Online Claims: Overcoming Challenges in BPJS Ketenagakerjaan's Digital Transformation Journey - Doris Febriyanti; Elvira Gustia Putri; Siti Zubaidah (Government & Resilience, 2025)
This study aims to determine the dynamics of the implementation of the BPJS/Indonesian Social Security Administering Body for Employment claim service system in the Old Age Security (JHT) program. The researcher also aims to analyze the factors inhibiting the online BPJS Employment claim process using the Jamsostek Mobile (JMO) application in Palembang City. This research used is a qualitative method with a descriptive approach. The data sources used are primary data sources in the form of interviews, secondary data sources in the form of journals, and books. The results of the research conducted, the implementation of JHT claims through online applications has been running in accordance with the digitization system. However, there are still obstacles that hinder the implementation of claims, namely less than optimal socialization to BPJS participants regarding how to claim through online applications, thus causing delays in the claim process due to incomplete documents. In addition, researchers saw obstacles that participants were not accustomed to using online applications, failed to upload documents during registration, and failed due to unstable participant internet networks. Therefore, in implementing online claim services, there needs to be a collaborative effort between BPJS and various parties so that BPJS deserves to be a protector for workers in Indonesia.